Synapse Formation and Function Across Species: Ancient Roles for CCP, CUB, and TSP-1 Structural Domains - González-Calvo, Inés; Cizeron, Mélissa; Bessereau, Jean-Louis; Selimi, Fekrije (Frontiers in Neuroscience, 2022)
The appearance of synapses was a crucial step in the creation of the variety of nervous systems that are found in the animal kingdom. With increased complexity of the organisms came a greater number of synaptic proteins. In this review we describe synaptic proteins that contain the structural domains CUB, CCP or TSP-1. These domains are found in invertebrates and vertebrates, and CUB and CCP domains were initially described in proteins belonging to the complement system of innate immunity. Interestingly, they are found in synapses of the nematode C. elegans, which does not have a complement system, suggesting an ancient function. Comparison of the roles of CUB-, CCP- and TSP-1 containing synaptic proteins in various species shows that in more complex nervous systems, these structural domains are combined with other domains and that there is partial conservation of their function. These three domains are thus basic building blocks of the synaptic architecture. Further studies of structural domains characteristic of synaptic proteins in invertebrates such as C. elegans and comparison of their role in mammals will help identify other conserved synaptic molecular building blocks. Furthermore, this type of functional comparison across species will also identify structural domains added during evolution in correlation with increased complexity, shedding light on mechanisms underlying cognition and brain diseases.